2020
DOI: 10.2196/21439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictive Models for COVID-19: Systematic Study

Abstract: Background COVID-19 is a rapidly emerging respiratory disease caused by SARS-CoV-2. Due to the rapid human-to-human transmission of SARS-CoV-2, many health care systems are at risk of exceeding their health care capacities, in particular in terms of SARS-CoV-2 tests, hospital and intensive care unit (ICU) beds, and mechanical ventilators. Predictive algorithms could potentially ease the strain on health care systems by identifying those who are most likely to receive a positive SARS-CoV-2 test, be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 59 publications
1
84
0
1
Order By: Relevance
“…Two recent studies ( 24 , 25 ) reported their results by using relatively larger data sets from clinical centers (one from Brazil with 558 COVID-19–positive chest radiographs and the other from the Netherlands with 980 COVID-19–positive chest radiographs used in both training and testing data sets). Schwab et al ( 24 ) trained a small number of conventional machine learning algorithms from their data set and reported an AUC of 0.66 (95% CI: 0.63, 0.70). In Murphy et al ( 25 ), a deep learning model was trained by using 512 COVID-19–positive chest radiographs combined with 482 COVID-19–negative chest radiographs and reported an AUC of 0.81 on chest radiographs in 454 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies ( 24 , 25 ) reported their results by using relatively larger data sets from clinical centers (one from Brazil with 558 COVID-19–positive chest radiographs and the other from the Netherlands with 980 COVID-19–positive chest radiographs used in both training and testing data sets). Schwab et al ( 24 ) trained a small number of conventional machine learning algorithms from their data set and reported an AUC of 0.66 (95% CI: 0.63, 0.70). In Murphy et al ( 25 ), a deep learning model was trained by using 512 COVID-19–positive chest radiographs combined with 482 COVID-19–negative chest radiographs and reported an AUC of 0.81 on chest radiographs in 454 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction performance of these models varied: the accuracy of these models in predicting COVID-19 was between 0.8 and 0.96 [ 30 - 32 ]. In addition, most of the reported ML models for the diagnosis or prediction of COVID-19 have involved more types of variables, such as CT results, clinical symptoms, and CLIs [ 17 , 32 , 33 ]. Although most of these COVID-19-related ML models were built with more than two ML algorithms, not all models constructed with each algorithm showed high performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these COVID-19-related ML models were built with more than two ML algorithms, not all models constructed with each algorithm showed high performance. The methods of feature selection that were used in these studies included the recursive feature elimination algorithm [ 31 ], causal explanation models [ 17 ], and the least absolute shrinkage and selection operator regression [ 32 ]. These methods can extract the features that are closely related to the target phenotype, but whether the classifier constructed by the combination of these features has the best performance needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide-association studies (GWAS) of COVID-19 are rather at the beginning but are highly promising to reveal critical illness cases (22,23). For data gathering, diagnostics and prediction models machine and deep learning techniques and applications of artificial intelligence are of utmost importance but also need to be critically reviewed (24)(25)(26)(27)(28)(29). Altogether, there is a risk that classical medical knowledge, especially qualitative, and intuitive knowledge of organismic pathology, will be lost before the transition to MSM can be implemented clinically.…”
Section: From Molecular To Organismal Systems Medicinementioning
confidence: 99%